A generic approach to estimate airborne concentrations of substances released by indoor spray processes using a deterministic 2-box model - Hahn, Stefan; Schwarz, Katharina; Nowak, Norman; Schwarz, Janine; Meyer, Jessica; Koch, Wolfgang (Frontiers in Public Health, 2024)
Sprays are used both in workplace and consumer settings. Although spraying has advantages, such as uniform distribution of substances on surfaces in a highly efficient manner, it is often associated with high inhalation burden. For an adequate risk assessment, this exposure has to be reliably quantified. Exposure models of varying complexity are available, which are applicable to spray applications. However, a need of improvement has been identified. fraction, room spraying should be used as a worst-case. The model scope may be extended to (semi)volatile substances. However, acceptance may be compromised by the limited availability of measured data for this group of substances and thus may have limited potency to evaluate the model prediction.